Case Report: Anterior Cruciate Ligament Calcification in a Patient With Chondrocalcinosis: Micro-Computed Tomography Presentation - Grassi, Alberto; Dal Fabbro, Giacomo; Fini, Milena; Zaffagnini, Stefano; Parrilli, Annapaola (Frontiers in Surgery, 2021)
In this case report an incidental post-operative diagnosis of anterior cruciate ligament (ACL) calcification, associated with calcification of posterior cruciate ligament (PCL) and lateral meniscus insertions, was made using micro Computed Tomography (µCT) technology in a knee specimen obtained during a total knee replacement surgery due to painful tri-compartmental osteoarthritis with chondrocalcinosis signs at pre-operative X-ray. ACL calcification is an uncommon find and conventional X-ray and MRI are not so helpful in its identification. µCT scan, in contrast, is of interest because it provides highly spatial 3-dimensional information with excellent visualization of bones and calcifications. The µCT technology used in this case report allowed to perform a detailed analysis and a 3-D reconstruction of the calcium pyrophosphate dihydrate (CPPD) crystal deposition about the knee without the need to section the specimens into slice as perfomed in previous studies. The 3-D model obtained with µCT scan permits to gain more insight into the shape of the calcification within the fibers of the ligamentous structures of the joint.